BS34 Telomere damage promotes vascular smooth muscle cell senescence and immune cell recruitment after vessel injury. (4th June 2021) - Grootaert, Mandy; Uryga, Anna; Garrido, Abel; Oc, Sebnem; Foote, Kirsty; Chappell, Joel; Finigan, Alison; Rossiello, Francesca; d'Adda di Fagagna, Fabrizio; Aravani, Dimitra; Jorgensen, Helle; Bennett, Martin
Abstract : Aim: Vascular smooth muscle cells (VSMCs) accumulate in injury-induced neointimal lesions and atherosclerotic plaques in an oligoclonal fashion, yet plaque VSMCs show reduced proliferation and cell senescence. DNA damage leads to VSMC senescence and inflammation, and VSMC senescence promotes atherosclerosis; however, the exact mechanism by which VSMC senescence promotes lesion formation is not known. Here, we investigated telomere damage-induced VSMC senescence, the contribution of senescence-induced inflammation and the mechanisms involved, the consequences of VSMC senescence in vivo after injury, and whether it promotes clonality. Methods: Stress-induced premature senescence (SIPS) was induced by the chemotherapeutic doxorubicin (24h treatment + 21d recovery). Lentiviruses were used to stably overexpress a dysfunctional TRF2 mutant protein (TRF2T188A) in human VSMCs (hVSMCs). SM22aTRF2T188A mice were generated that express human TRF2T188A in VSMCs only, and crossed with Myh11-CreERT2 Rosa26-Confetti multicolour reporter mice, to study cell senescence and clonality in vivo. Arterial injury was induced in these mice by ligation of the left common carotid artery for 28 days. Results: Both SIPS and TRF2188A-induced VSMC senescence were characterised by persistent telomere damage, and associated with formation of micronuclei, activation of cGAS-STING cytoplasmic DNA sensing, and induction of multiple pro-inflammatory cytokines. Silencing of cGAS in TRF2T188A hVSMCs partially inhibited NFkB-dependent cytokine expression. In vivo, VSMC-specific TRF2T188A expression in a multicolour clonal VSMC-tracking model demonstrated no change in VSMC clonal patches after injury, but increased neointima formation ( figure 1 ), outward remodelling and cellular senescence. Moreover, neointimal lesions of VSMC-specific TRF2T188A mice were characterised by increased ICAM1 expression and increased abundance of CD45+, CD3+ and CD68+ cells when compared to littermate controls, indicating increased immune/inflammatory cell infiltration and/or retention. Conclusions: Persistent telomere damage promotes VSMC senescence and inflammation, and exacerbates neointima formation after injury. Our data suggest that persistent telomere damage-induced VSMC senescence plays a major role in driving inflammation through immune cell recruitment in vascular disease. Targeting senescence and senescence-associated inflammation in particular, could limit injury-induced neointima formation and neoatherosclerosis. Conflict of Interest: No